The software value map — an exhaustive collection of value aspects for the development of software intensive products. Issue 7 (27th June 2012) - Khurum, Mahvish; Gorschek, Tony; Wilson, Magnus
SUMMARY In software intensive products such as cars or telecom systems, software has traditionally been associated with cost, and there has been no real perception of its value in relation to the entire product offering. However, because software is becoming a larger part of the main competitive advantage, driving innovation and product differentiation, hardware is becoming more standardized, thus the valuation of software is becoming critical. In existing literature, several value constructs and corresponding valuation/measurement solutions needed for making decisions about software product development are presented. However, the contributions are often isolated with respect to a certain perspective such as focusing on product's internal or external quality aspects only. Consequently, a complete view of value constructs relevant from different perspectives required for making decisions about software product development is missing. This paper presents a consolidated view of the software value concept utilizing the major perspectives and introduces a software value map. The created value map was evaluated through an industry case study through the development of impact evaluation patterns, which were subsequently used by professionals in industry, and experiences gathered. During industry evaluation, practitioners found substantial benefits of having a consolidated, vastly improved, and extended value aspect's view of software. Copyright © 2012 John Wiley & Sons, Ltd.